(untitled) (Editora Impacto Científico, 2025)
Maraging steels constitute a class of ultra-high-strength steels characterized by high alloy and low carbon content. These materials are widely used in the aerospace and nuclear sectors due to the combination of properties such as high mechanical strength, good ductility, and high fracture toughness, and can reach yield strengths close to 2000 MPa after aging heat treatment. Overaging is a phenomenon associated with aging heat treatment at elevated temperatures for long periods, resulting in a reduction in mechanical strength. The objective of this work was to evaluate the effect of overaging on maraging steel 300, considering the variables of temperature (500, 550, and 600 °C) and time (3, 5, and 6 hours) of heat treatment. Different heat treatment conditions were compared through the characterization of mechanical properties, determined by Rockwell C hardness (HRC) and tensile tests, and the identification of the phases present by X-ray diffraction (XRD). The results indicated that the lowest tensile strength limit was obtained at 600 °C for 6 hours. In this temperature range, no statistically significant differences were observed between the 5 and 6 hour times, evidencing greater susceptibility to the overaging phenomenon. DOI: https://doi.org/10.56238/edimpacto2025.090-056